Diabetes transition care and adverse events: a population‐based cohort study in Ontario, Canada. Issue 11 (3rd August 2018) - Shulman, R.; Shah, B. R.; Fu, L.; Chafe, R.; Guttmann, A.
Abstract: Aims: To describe patterns of primary and diabetes care during transition age (17 to < 19 years) into early adulthood (age 19 to 26 years), and to evaluate the association of primary and diabetes care patterns during transition age with the risk of adverse events in early adulthood. Methods: We conducted a population‐based cohort study of individuals in Ontario, Canada who were diagnosed with diabetes aged < 15 years and who turned 17 between November 2006 and March 2011, followed until March 2015 ( n = 2525). Using linked administrative databases, we examined healthcare use during: 'pre‐transition‐age' (15 to < 17 years), 'transition‐age' (17 to < 19 years), and 'early adulthood' (19 to 26 years). The main outcomes were time to death or ketoacidosis and rate of diabetes‐related admissions. The main exposures were the gap in diabetes care and primary care visits during transition age. Results: There were < 6 deaths and 446 individuals (17.7%) had at least one admission for ketoacidosis during early adulthood. In all, 1188 individuals (47.0%) had a > 12‐month gap in diabetes care and 241 (9.5%) had no primary care visits during transition age. A gap in diabetes care of > 12 months and no primary care visits during transition age were associated with an increased risk of ketoacidosis or death (adjusted hazard ratio 1.31, 95% CI 1.04–1.66 and adjusted hazard ratio 1.42, 95% CI 1.02–1.97, respectively). Conclusions: In Ontario, Canada, where physician and hospital‐based services are universally covered, a high proportion of young adults with diabetes have insufficient care during transition age and this is associated with a higher risk of important adverse outcomes in early adulthood. Ensuring primary care involvement during transition may be a strategy to reduce morbidity. What's new?: This is the first population‐based study of the relationship between patterns of primary and diabetes care during transition and adverse events in early adulthood. The patterns of care during transition age that we observed showed deficiencies in both diabetes and primary care. A gap in diabetes care of > 12 months and lack of primary care visits during transition age are markers for worse outcomes in early adulthood. Further work is needed to determine the optimal way to integrate primary care into transition processes.